Perlindungan Hukum terhadap Hak Pendesain Industri Atas Gugatan Pembatalan Pendaftaran Desain Industri (Studi Putusan MA No. 407.K/PDT.SUS/HKI) - Nugraha, Aga Rudiansyah; Nadirah, Ida; Limbong, Ferry Susanto (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
The purpose of this study is an attempt to analyze the legal protection of industrial design rights over lawsuits for cancellation of industrial design registrations. The research method used is using normative legal research methods with literature study data collection techniques, the analysis of this research is decision analysis. The result of this research is that the legal protection for the rights of industrial designers who have registered for the lawsuit for the cancellation of the registration of industrial designs is that the legal protection against the lawsuit for cancellation can be given through the registration mechanism. Protection can be obtained if an industrial design has been registered. This makes it easier to prove and protect even though the principle is from the emergence of industrial design matters. An industrial design right certificate can be issued at the Director General of Intellectual Property Rights which has an important role as proof of ownership for industrial design rights so that it does not have an element of novelty. The conclusion of this study is the legal considerations of the Supreme Court judges on the lawsuit for the cancellation of industrial design rights which have been registered in the Supreme Court's decision no. 407.K/PDT.SUS/HKI/2019 has fulfilled a sense of justice because it does not have a juridical basis and provides legal protection to registered industrial design rights as well as legal certainty if the plaintiff who files a lawsuit for the cancellation of the registered industrial design right cannot prove that the industrial design rights are in accordance with the applicable laws and regulations.